Aristotle on the Origin of Theoretical Sciences (Met. A 1–2) - Verlinsky, Alexander (Hyperboreus, 2019)
In his classic statement in the introductory part of the Metaphysics (ch. 1), Aristotle asserts that theoretical knowledge emerged earliest in the countries where leisure has been attained and adds that, for that reason, the mathematical sciences appeared ﬁrst in Egypt, because there the priests were allowed to have leisure. According to the scholarly view prevailing nowadays, Aristotle assigns to the appearance of leisure the crucial role in the emergence of theoretical knowledge. Scholars agree that the appearance of leisure in Greece was an important, although not the sole condition for the emergence of theoretical knowledge and for its rapid progress. They maintain at the same time that Aristotle errs when he ﬁnds in Egypt mathematics that resembled Greek mathematics both in their deductive character and in their theoretical purposes and that he errs when he assigns to priests the decisive role in the development of mathematical knowledge. On the contrary, W. Spoerri used the preceding part of Aristotle’s reasoning to prove that his genuine explanation consists in the gradual development of practical kinds of knowledge: they satisﬁed material needs and released human forces for the pursuit of the non-utilitarian truths of theoretical sciences; according to Spoerri, the leisure of Egyptian priests is superﬂuous for this explanation and was probably inserted from another of Aristotle’s treatises. The author argues that both these interpretations are unjust to the text of the Metaphysics and to the complexity of Aristotle’s explanation, which embraces both general social-psychological preconditions for the emergence of theoretical knowledge and speciﬁc favourable ones for its emergence precisely in Egypt. Aristotle notices that already the inventors of the earliest crafts, which produce vitally necessary things, were admired not only because of the utility of their inventions (this utility does not greatly surpass the experience that had already been accumulated in the same ﬁeld), but because of the intrinsic value, the ‘wisdom’ of their achievements – the classiﬁcation of recurrent phenomena that have been ﬁxed by experience, the grasping of their causes and the new capacity to transmit knowledge to other persons who do not have their experience. At the next stage of development, the inventors of the τέχναι that were pertinent to leisure amusements (music, poetry, painting, sculpture) were esteemed as ‘wiser’ than the inventors of necessary things, because the society grew to value the excellence of knowledge more than its practical utility. Aristotle explains the beginning of the pursuit of theoretical knowledge (along with the factors inherent in knowledge – the accumulation of experience due to practice in the ﬁelds of mathematics and astronomy) by the attainment of the limit in the development of both kinds of τέχναι. Once this limit had been attained and further improvements did not evoke more admiration, the inborn human desire to ﬁnd explanations now turned systematically to problems that were not related to practical utility. The society was also now prepared to ‘admire’, viz. to encourage and materially support, the intellectual search in the ﬁeld of non-practical knowledge. These generalisations are valid for the development of knowledge as a whole, but when speaking about Egypt as the land in which mathematics appeared, Aristotle also has in view the speciﬁc Egyptian institution, the caste system: it provided to the Egyptian priests freedom from military and administrative duties and released them from care for their material needs. This probably means that, due to these favourable conditions, the priests became the kind of people among whom the ﬁrst theoretical scientists appeared when the society was prepared to encourage their studies. Aristotle is mistaken, of course, when he ﬁnds theoretical mathematics in Egypt, but he does not extrapolate to Egypt the leisure that is typical of Greece – the leisure of intellectuals as dependent on accidental family conditions, payment for teaching or the generosity of sponsors. The leisure Aristotle has in view is the unique product of Egypt’s extraordinary political system, viz. state support for scientiﬁc knowledge.